The Moral Status of Persons Perspectives on Bioethics - Becker, Gerhold K. (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The advances in molecular biology and genetics, medicine and neurosciences, in ethology and environmental studies have put the concept of the person firmly on the philosophical agenda. Whereas earlier times seemed to have a clear understanding about the moral implications of personhood and its boundaries, today there is little consensus on such matters. Whether a patient in the last stages of Alzheimer's disease is still a person, or whether a human embryo is already a person are highly contentious issues. This book tackles the issue of personhood and its moral implications head-on. The thirteen essays are representative of the major strands in the current bioethical debate and offer new insights into humanity's moral standing, its foundations, and its implications for social interaction. While most of the essays approach the issue by drawing on the rich intellectual tradition of the West, others offer a cross-cultural perspective and make available for ethical consideration the philosophical resources and the wisdom of the East. The contributors to this book are highly recognized philosophers, ethicists, theologians, and professionals in health care and medicine from East Asia (China, Japan), Europe, and North America. The first part of the book probes the foundations of personhood. Examining critically the main theories on personhood in contemporary philosophy, the authors offer alternatives that better respond to contemporary challenges and their implications for bioethics. The focus of the second part is firmly on the Confucian relational concept of the person and on the social constitution of personhood in traditional Japanese culture. While the essays challenge the individualistic features of personhood in the Western tradition, they lay the foundations for a richer concept that holds great promise for the resolution of moral dilemmas in modern medicine and health care. The third part of the book enters into a dialogue with the Christian tradition and draws on its spiritual heritage in the search for answers to the contemporary challenges to human dignity and value. Its focus is on the Catholic social thought and Lutheran theology. The fourth part addresses the moral status of persons in view of specific issues such as the effects of brain injury, gene therapy, and human cloning on personhood. It extends the scope of research beyond human beings and inquires also into the moral status of animals.